A presença de Kaiser no Quadro Teórico do Tratamento Temático da Informação (TTI) - Sales, Rodrigo de [UNESP] (2012)
The systematic indexing developed by the German librarian Julius Otto Kaiser at the end of the nineteenth and the beginning of the twentieth centuries brought groundbreaking contributions to the theoretical framework of the Subject Approach to Information (SAI). Neverthless, the SAI literature usually refers to Kaiser more through the subject analysis based on the concrete-process binomy than through the pioneering development of indexing as a method to construct indexes. This study addresses Kaiser as a theoretical reference in the SAI universe by proposing that Kaiser’s conception of systematic indexing established the pillars of the synthetic analytical methods, which, in turn, was the basis for the development of Ranganathan’s faceted classification. The theoretical framework on which this study is based is comprised by the literature produced by the Anglo-American approaches, namely bibliographic classification, subject cataloguing and indexing. To do so, we put Kaiser’s professional career in the SAI scenario, showing his theoretical dialogues with other exponents of the area, which set him on the same level as others such as Otlet, Cutter and Ranganathan. For our methodological approach, we adopted the pragmatism of William James – which focuses on taken paths and the possibilities of accomplishment –, we investigated how the systematic procedures of Kaiser’s indexing method can appear as a pioneer of the synthetic analytical method. Pragmatic observation was empirically supported by the analysis of Kaiser’s works, which constitute a crucial body of investigation. The analytical and synthetic dimension in Kaiser’s works allows the definition of variables used to relate his method with Ranganathan’s. Based on such variables (elements of the analysis, development of analysis, development of synthesis and the products... (Complete abstract click electronic access below)